Comparative analysis of strategies for adapting migration legislation in Spain and the United States to the needs of Ukrainian refugees - Fursenko, Nataliia (Український політико-правовий дискурс, 2025)
The relevance of the study is due to the unprecedented scale of forced migration of Ukrainian citizens caused by Russian armed aggression, which has necessitated the rapid transformation of legal mechanisms for regulating migration processes. Under these conditions, particular importance is attached to examining the effectiveness of different legal response models capable of ensuring a balance between the prompt provision of protection, respect for human rights, and opportunities for the socio-economic integration of displaced persons. The aim of the article is to identify and scientifically generalize the differences in strategies for adapting migration legislation in Spain (within the legal framework of the European Union) and the United States of America to the needs of Ukrainian refugees, as well as to assess their effectiveness from the perspective of ensuring legal protection and integration. The methodological basis of the research consists of general scientific and specialized legal methods, including formal-legal, comparative-legal, system-structural, and normative-analytical methods. The application of these methods enabled the examination of the content and interrelation of legal acts, the determination of the legal nature of the relevant legal instruments, and the comparison of their functions. The study establishes that the European model, implemented through the temporary protection mechanism, provides for the centralized introduction of a unified legal status that integrates key socio-economic rights and ensures a rapid response to the mass influx of displaced persons. In contrast, the American model is based on the application of a set of autonomous immigration instruments, including asylum, refugee status, temporary protection, and humanitarian parole, which results in an individualized determination of legal status and a differentiated scope of rights. It is substantiated that the key criteria distinguishing the legal strategies for adapting migration legislation in Spain (within the framework of the European Union) and the United States of America include the legal nature of the status of Ukrainian refugees, the level of procedural formalization, the degree of administrative discretion, and the nature of their social integration. It is proven that the European approach has a clearly defined socio-integration orientation and ensures unified access to fundamental rights for Ukrainian refugees, whereas the American model is focused on immigration control and individualized regulation of the legal status of displaced persons.